Relative Abundance and Species Richness of Toads in UNIMAS College Campus (UCC) - Naveen, Gopal (Universiti Malaysia Sarawak (UNIMAS), 2022)
Toads play a major role in maintaining the ecosystem such as controlling insect population by feeding on them or to serve as food source to predators such as snakes and bird and it is important to ensure that the population of toads will continue to thrive in future. This study examines the relative abundance, number of toad species, correlation between relative humidity and temperature on toads’ abundance and the horizontal microhabitat use of toads in west and east UNIMAS. The sampling method used in this study was Visual Encounter Survey method along a line transect and the measurement of toads such as snout-vent length, tibia length and weight were recorded. A total of 35 individuals of toads were sampled from both west and east UNIMAS comprising of two species Duttaphrynus melanostictus and Ingerophrynus quadriporcatus. A negative correlation (- 0.13) was obtained for temperature and a positive correlation (0.62) for relative humidity in west UNIMAS whereas a contradictory result, positive correlation (0.80) for temperature and negative corelation (- 0.80) for relative humidity was obtained in east UNIMAS. The horizontal microhabitat where the toads were sampled indicates that permanent pond on bank distance to water is the preferred microhabitat by the toads.